2018 European Thyroid Association (ETA) Guidelines on the Diagnosis and Management of Central Hypothyroidism. Issue 5 (19th October 2018) - Persani, Luca; Brabant, Georg; Dattani, Mehul; Bonomi, Marco; Feldt-Rasmussen, Ulla; Fliers, Eric; Gruters, Annette; Maiter, Dominique; Schoenmakers, Nadia; van Trotsenburg, A.S. Paul
Abstract : Objectives: Central hypothyroidism (CeH) is a rare form of hypothyroidism characterized by insufficient thyroid stimulation due to disturbed pituitary and/or hypothalamic functioning. Due to its origin and the whole clinical context, CeH represents a challenging condition in clinical practice as it is characterized by suboptimal accuracy of clinical and biochemical parameters for diagnosis and management. Since no expert consensus or guidance for this condition is currently available, a task force of experts received the commitment from the European Thyroid Association (ETA) to prepare this document based on the principles of clinical evidence. Study Design: The task force started to work in February 2017 and after a careful selection of appropriate references (cohort studies, case reports, expert opinions), a preliminary presentation and live discussion during the 2017 ETA meeting, and several revision rounds, has prepared a list of recommendations to support the diagnosis and management of patients with CeH. Results: Due to the particular challenges of this rare condition in the different ages, the target users of this guidance are pediatric and adult endocrinologists. Experts agreed on the need to recognize and treat overt CeH at all ages, whereas treatment of milder forms may be dispensable in the elderly (> 75 years). Conclusions: Despite the lack of randomized controlled clinical trials, the experts provide 34 recommendations supported by variable levels of strength that should improve the quality of life of the affected patients and reduce the metabolic and hormonal consequences of inadequate management.